2018
DOI: 10.1002/jmrs.281
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Specialist Radiation Therapist (CSRT): A case study exploring the effectiveness of a new advanced practice role in Canada

Abstract: IntroductionThe Clinical Specialist Radiation Therapist (CSRT), is a new advanced practice (AP) role for radiation therapists (RTTs). Following training, education and evaluation, the CSRT performs specific duties in autonomous ways, making advanced clinical decisions in their area of specialization. This case study examines the CSRT's impact on quantity (i.e., increasing capacity), improving quality and stimulating research and innovation.MethodsBetween 2007 and 2016, 23 CSRTs worked in 10 cancer centres in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 16 publications
1
45
0
2
Order By: Relevance
“…The need for a formalized framework for RTs to expand their practice is well documented [9][10][11][12]; despite this need, there seems to have been little done implementing this in Australia and New Zealand. In Ontario, Canada an advanced practice Clinical Specialist Radiation Therapist (CSRT) role and practice framework has been successfully implemented [12,13]. This has relieved local workforce pressures while allowing RTs to work at the full scope of their practice [9,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The need for a formalized framework for RTs to expand their practice is well documented [9][10][11][12]; despite this need, there seems to have been little done implementing this in Australia and New Zealand. In Ontario, Canada an advanced practice Clinical Specialist Radiation Therapist (CSRT) role and practice framework has been successfully implemented [12,13]. This has relieved local workforce pressures while allowing RTs to work at the full scope of their practice [9,12].…”
Section: Discussionmentioning
confidence: 99%
“…Several factors such as limited opportunities for professional development, working conditions and issues with management have been identified in the literature to influence a RTs intent to leave the profession [8]. The issue of RT career advancement has been well documented [9][10][11][12][13]. Halkett et al [14] found that RTs perceived that there were limited opportunities to specialise and that any further education had little chance of being recognised.…”
Section: Introductionmentioning
confidence: 99%
“…À moyen terme, il est pertinent d’envisager une nouvelle fonction de manipulateur en pratique avancée en radiothérapie (CSRT pour clinical specialist radiation therapist ) afin de faire face aux changements induits par la radiothérapie hypofractionnée. L’apport de cette nouvelle fonction a été évalué au Canada de 2007 à 2016 dans dix centres de radiothérapie [35] . Elle permet d’améliorer la qualité des soins dispensés aux patients et de faciliter les progrès de la science et de la pratique de la radiothérapie, tout en augmentant la capacité de prise en charge de patient, l’efficience des différentes étapes du workflow et la satisfaction des patients, des manipulateurs et de l’encadrement.…”
Section: Discussionunclassified
“…Motivated individuals have developed clinical, technical and professional competencies relevant to the operations of their programmes and brought about meaningful change by working more autonomously within them. By performing duties traditionally carried out by radiation oncologists and initiating programmatic changes, wait times have decreased, and patient throughput and system capacities have improved [42].…”
Section: Advancing Roles Within the Multidisciplinary Teammentioning
confidence: 99%